Neospora caninum and Ehrlichia canis co‐infection in a dog with meningoencephalitis. (6th February 2018) - Aroch, Itamar; Baneth, Gad; Salant, Harold; Nachum‐Biala, Yaarit; Berkowitz, Asaf; Shamir, Merav; Chai, Orit
Abstract: An 8‐year‐old mixed‐breed dog was presented for acute, progressive weakness and ataxia, inappetence, and weight loss. The patient was mentally normal, but nonambulatory, with a right head tilt, right positional ventral strabismus, and slight head tremors. A neurologic lesion was localized to the cerebellum and right brainstem. Cerebrospinal fluid (CSF) analysis showed a markedly increased protein concentration and mixed pleocytosis, with eosinophil predominance (44%), intracytoplasmic inclusions within eosinophils, consistent with Ehrlichia canis ( E canis ) morulae, and Toxoplasma gondii ( T gondii ) or Neospora caninum ( N caninum ) tachyzoites within eosinophils and monocytes. A serum indirect immunofluorescent antibody test was positive for N caninum (titer 1:12 800) and negative for T gondii . Both blood and CSF PCR results were N caninum‐ and E canis ‐positive and T gondii ‐ and Anaplasma phagocytophilum ‐negative, and blood PCR, but not CSF PCR, was Hepatozoon canis‐ positive. The dog was treated for 30 days with clindamycin, sulfamethoxazole‐trimethoprim, doxycycline, prednisone, and cephalosporin, but did not improve neurologically, and was euthanized. Brain histopathology showed moderate multifocal, subacute meningoencephalitis with necrosis and gliosis. The neurologic disease was mostly attributed to central nervous system (CNS) neosporosis, with the possible contribution of ehrlichiosis, which was likely a manifestation of blood‐brain barrier disruption. Hepatozoonosis was probably a result or cause of underlying immunosuppression. To our knowledge, this is the first report of CNS N caninum and E canis co‐infection detected by both CSF PCR and cytology and E canis morulae identified within CSF eosinophils.